ESG transition: the green agenda in the global financial economy ("Journal "U". Economy. Management. Finance.", 2025)
The purpose of the article is to systematize ideas about the ESG transition, greening economics and finance. The article reveals the essence of ESG criteria and ESG risks taken into account in investment decisions, analyzes the most significant aspects characterizing the impact of the ESG transition on the global economy and finance, and assesses the readiness of the banking sector to operate in accordance with ESG principles.
Keywords: ESG-transition; sustainable finance; new paradigm of the global economy; ESG-risks; ESG-criteria; green agenda